Penyelesaian Faktorisasi Koprima dengan Algoritma Euclid dan Metode Ruang Keadaan untuk Penentuan Pengendali yang Menstabilkan Sistem - Asmat, Asmat; Widowati, Widowati (JURNAL SAINS DAN MATEMATIKA, 2012)
Stability is the main requirement that must be met on the control system. If the plant from the control system is not stable, then the controller C can be searched so that the feedback system becomes internally stable. Let G be a transfer function represented by , where N, M are coprime factorization and element of family of all stable, proper, real rational function. Functions N and M can be found by using Euclidean algorithm and the state space method. Further, we find controller, that satisfy, NX + MY = I, so that the feedback system is internally stable. To verify the proposed method, numerical examples are given. Keywords: Euclidean algorithm, coprime factorization, state space method, controller, stable